(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article aims to provide future teachers of mathematics and informatics with excellent knowledge and skills in specialized subjects, which are aimed at ensuring the coherence of subjects suitable for their fields. dedicated to the preparation and disclosure of educational programs. Teachers of mathematics and informatics study the content of specialized subjects mainly on the basis of a separate tendency or consider the possibilities of solving certain standard tasks with the help of electronic resources.